Pengaruh Viral Marketing, Product Quality dan Taste of Burger King terhadap Purchase Decision Konsumen Burger King di Kota Bandung - Azriel Muhamad Sani; Akbar Rohandi, Mochamad Malik (Bandung Conference Series: Business and Management, 2024)
Abstract, Such rapid growth in the fast food industry can be felt in the city of Bandung. This can be seen from the large number of fast food restaurants found. So, there needs to be an appropriate strategy so that consumers decide to purchase the products being sold. Fast food restaurants can use digital marketing methods by using viral marketing on social media platforms.Apart from that, fast food restaurants also need to maintain and improve product quality and taste in the food and beverage products they sell and make them unique compared to competitors' products. This research aims to analyze "The Influence of Viral Marketing, Product Quality and Taste of Burger King on Purchase Decisions of Burger King Consumers in Bandung City".This research uses quantitative research methods by conducting an associative analysis approach. The object of this research is consumers who have visited and shopped at Burger King outlets in Bandung. Samples were taken using a purposive sampling technique and the number was determined using the Hair formula.In the research, statistical testing was used in the form of classical assumption tests, correlation tests, determination tests, multiple linear regression tests, t tests and F tests.Based on descriptive research, it is known that overall Viral Marketing, Product quality, Taste and Purchase Decision at Burger King in Bandung are in the good category.Meanwhile, the results of the research verified that Viral Marketing, Product Quality, and Taste of Burger King had a significant positive effect on Purchase Decisions, both partially and simultaneously. Viral Marketing, Product Quality, and Taste Of Burger King have a strong relationship with Purchase Decision. Abstrak, Pertumbuhan yang begitu pesat dalam industri makanan cepat saji dapat dirasakan di kota Bandung. Hal ini dapat dilihat dari banyaknya dijumpai restoran cepat saji. Sehingga, perlu adanya strategi yang tepat agar konsumen memutuskan melakukan pembelian terhadap produk yang dijual. Restoran cepat saji dapat menggunakan metode pemasaran digital dengan menggunakan viral marketing pada platform media sosial. Selain itu, restoran cepat saji juga perlu mempertahankan dan meningkatkan produk quality dan taste pada produk makanan dan minuman yang dijual dan menjadi unik daripada produk pesaing. Penelitian ini memiliki tujuan untuk menganalisa “Pengaruh Viral Marketing, Product Quality dan Taste Of Burger King Terhadap Purchase Decision Konsumen Burger King di Kota Bandung”. Penelitian ini menggunakan metode penelitian kuantitatif dengan melakukan pendekatan analisis asosiatif. Objek penelitian ini yaitu konsumen yang pernah berkunjung dan berbelanja di gerai Burger King di Bandung. Sampel diambil dengan menggunakan teknik purposive sampling dan jumlahnya ditentukan dengan rumus Hair. Dalam penelitian digunakan pengujian statistic dalam bentuk uji asumsi klasik, uji korelasi, uji determinasi, uji regresi linier berganda, uji t dan uji F. Berdasarkan penelitian secara deskriptif diketahui bahwa Viral Marketing, Product quality, Taste dan Purchase Decision pada Burger King kota Bandung secara keseluruhan berada pada kategori baik. Sedangkan hasil penelitian secara verifikatif diketahui bahwa Viral Marketing, Product Quality, dan Taste Of Burger King berpengaruh positif signifikan terhadap Purchase Decision baik secara parsial maupun secara simultan. Viral Marketing, Product Quality, dan Taste Of Burger King memiliki hubungan yang kuat dengan Purchase Decision.